Recovery Management in Business-to-Business Markets Conceptual Dimensions, Relational Consequences and Financial Contributions - Döscher, Kristian. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
The book is related to the handling of product and service failures in business-to-business markets. The concept of “recovery management” embraces all activities of seller firms to effectively handle failure situations in order to restore customer satisfaction and attain customer retention. Since prior research on recovery management has been mostly related to business-to-consumer (B2C) markets and business-to-business markets (B2B) reflect significantly different characteristics, a context-specific approach to handle product or service failures in B2B markets is required by researchers and practitioners alike. Based on a profound qualitative and quantitative investigation, Kristian Döscher derives the fundamental conceptual dimensions and discloses the relational consequences as well as the financial contributions of recovery management in B2B markets. Contents Conceptual dimensions of recovery management in B2B markets Relational consequences of recovery management in B2B markets Financial consequences of recovery management in B2B markets  Target Groups Researchers and students in Business Management with a focus on B2B Sales & Marketing Professionals with a focus on B2B Sales & Marketing in industrial firms  The Author Kristian Döscher is Head of Marketing Original Equipment at a large automotive supplier firm in Germany and has worked in several Sales & Marketing positions.